Candi Keboireng: Aspek Keagamaan dan Kronologinya - Al Haq, Muhammad Azzam; Wirasanti, Niken (AMERTA, 2023)
Abstract. Keboireng Temple: Its Religious Aspects and Chronology. Various aspects of the existence of temples can be studied, one of which is the religious background underlying the construction of the temple. Generally, the identification of the religious background of temple buildings can be based on the presence of the main deity statue worshipped in the temple. However, not all temples are rediscovered in intact condition, one of which is the Keboireng Temple. Therefore, the identification of the religious background of Keboireng Temple is carried out by utilising the data of decorative elements (kāla), written source data (inscriptions and ancient manuscripts), and toponyms. The kāla of Keboireng Temple is unique because it is depicted grasping and biting an object until it bends. Such a depiction of kāla is not commonly found. The Mūla Maluruŋ inscription mentions the existence of a place of worship of Bhairawa, one of the terrifying manifestations of the Hindu deity Śhiva, in Kapulungan. Other data sources were used to find the connection between the toponym of Kapulungan and Keboireng Temple. The analysis of the unique depiction of kāla, the description in the Mūla Maluruŋ inscription, and the identification of the Kapulungan toponym lead to the conclusion that Keboireng Temple in its original context was a temple for followers of the Bhairawa sect that flourished during the Siŋhasāri period. Keywords: Keboireng Temple, Religious Background, Kāla Ornament, Kapulungan, Bhairawa   Abstrak. Terdapat berbagai aspek yang dapat dikaji mengenai keberadaan candi, salah satunya adalah latar keagamaan yang mendasari pembangunan candi tersebut. Pada umumnya, identifikasi latar keagamaan bangunan candi dapat didasarkan pada keberadaan arca utama yang dipuja di candi. Namun, tidak semua candi ditemukan kembali dalam keadaan utuh, salah satunya adalah Candi Keboireng. Oleh karena itu, identifikasi latar keagamaan Candi Keboireng dilakukan dengan memanfaatkan data ragam hias (kāla), data sumber tertulis (prasasti dan naskah kuno), dan toponimi. Kāla Candi Keboireng memiliki keunikan karena digambarkan menggenggam dan menggigit sebuah objek hingga bengkok. Penggambaran kāla tersebut tidak umum dijumpai. Prasasti Mūla Maluruŋ menyebutkan adanya tempat pemujaan Bhairawa, salah satu manifestasi Dewa Śiwa dalam agama Hindu yang berwujud mengerikan, di Kapulungan. Sumber data lain digunakan untuk mencari keterkaitan antara toponimi Kapulungan dengan Candi Keboireng. Analisis terhadap penggambaran kāla yang unik, keterangan dalam prasasti Mūla Maluruŋ, serta identifikasi atas toponimi Kapulungan menghasilkan kesimpulan bahwa Candi Keboireng dalam konteks aslinya merupakan sebuah kuil untuk penganut aliran Bhairawa yang berkembang pesat pada masa Siŋhasāri.  Kata kunci: Candi Keboireng, Latar Keagamaan, Kāla, Kapulungan, Bhairawa